Livestock behaviour, management and welfare - Manteca i Vilanova, X.; Smith, A.J. (Technical Centre for Agricultural and Rural Cooperation, 2004)
Containing a wealth of information illustrated with photographs, diagrams and tables, this book provides detailed practical advice for stockholders in developing countries. The focus here is on cattle, sheep, goats, pigs and poultry, with the authors providing management suggestions for a range of different livestock production systems, both traditional and modern. Readers are also introduced to such issues as the behavioural aspects of reproduction and how to manage feeding behaviour for maximum productivity.